Pathogen Detection and Diagnostic Scenarios in Chronic Prostatitis - Vittorio Magri; Gianpaolo Perletti; Konstantinos Stamatiou (Diagnostics)
Background/Objectives: Chronic prostatitis (CP) is characterized by a variety of symptoms, including pelvic pain, urinary disturbances, and sexual dysfunction, often without clear signs of infection, which complicates its diagnosis. For decades, the NIH consensus definitions and the Meares–Stamey 4-glass test have been the cornerstone of diagnosing and classifying CP. However, emerging research suggests that some cases with negative microbiological findings may still respond to antibacterial therapy, potentially due to undiagnosed infections. This study aimed to compare four lower genito-urinary tract diagnostic methods to identify which is most effective at detecting causative pathogens in CP patients. Two simplified tests, each involving only two specimens, were also simulated. Methods: This retrospective study examined a database of patients diagnosed with chronic prostatitis according to NIH criteria. Patients aged 18–59 underwent clinical and microbiological diagnostic assessments using four testing modalities: the Meares–Stamey 4-glass “gold standard” test, the two-glass pre–post-massage test, and two tests incorporating post-massage semen samples, namely the five-glass test and the VB2-semen test. The diagnostic outcomes and pathogen detection rates for each test were compared using the ANOVA and the Pearson’s chi-squared tests. Results: Compared to the four-glass and two-glass tests, the five-glass and VB2-semen tests detected similar proportions of E. coli and other Gram-negative traditional prostatic pathogens. However, they were more effective in detecting significantly higher percentages of Enterococci. Moreover, the five-glass and VB2-semen tests, which included semen samples, identified a broader spectrum of pathogens and significantly higher proportions of sexually transmitted pathogens. Conclusions: Tests that included semen samples were more effective at detecting Gram-positive pathogens such as Enterococci and sexually transmitted pathogens. We advocate for incorporating semen samples into the standard four-glass test to enhance diagnostic accuracy and improve the targeted antibacterial treatment of chronic prostatitis.